Propagation of Aquatic Game Birds - McAtee, W. L. (Waldo Lee), 1883-1962 (United States. Government Printing Office., 1930)
"A surprisingly large number (nearly 50 species) of the ducks, geese, and swans of North America have been bred in captivity, most of them, however, upon only a small scale. About 20 species have been bred rather frequently either in this country or abroad, and at least one of them, the common mallard duck, can be propagated as readily as, if not more readily than, the ring-necked pheasant of the group of upland game birds. The directions for propagating here given apply primarily to the mallard and the Canada goose, the most frequently reared birds of their groups. These directions summarize the experience of the most successful breeders both in the United States and in Europe. Exceptional treatment found desirable in the care of other species is noted." -- p. 1